Violence in the Algerian city, an exploratory study in the city of Biskra - Tahar BRAHIMI (Social Sciences Journal, 1970)
The Algerian city knows various social problems that have become part of the consequences of daily life, sometimes reaching the level of familiar behaviour. Although they are rejected by custom and law, due to the intensity of their appearance, continuity and prevalence, they are in a position that crowds out the line of standards of indifference and trends of general social control. It is no secret that some of these problems are Living in the city or having a limited presence in it is a hardship that must be endured, and then discovering it by searching for its characteristics, effects and factors associated with it are all the priority of researchers and decision makers. Direct or indirect at the present time, or the fate of society or one of its systems, even if its degree differs. It deviates from the pattern of prevailing values and beliefs towards a disorder of social and cultural being, and is therefore similar to its colors in terms of type and quantity, with a line of two points that gradually descends and rises, as in its initial borders it is often It is not understood or given effective importance, and it is in its intensity pathological manifestations that are dangerous, disturbing, and violent.